Association of respirable cement mineral dust exposure with fractional exhaled nitric oxide and interleukin-8 on airways inflammation among cement workers in Negeri Sembilan, Malaysia - Kamaludin, Noor Haziqah (2020)
Prolonged exposure to cement dust may induce immunologic response due to high-level irritant-exposure. This study was to investigate the association of exposure to respirable cement mineral dust with the respiratory health performance by interpretation of Fractional Exhaled Nitric Oxide (FENO) and Interleukin-8 (IL-8) concentrations. A cross-sectional comparative study was carried out among 179 cement workers consist of manufacturing and administrative workers while 173 school staffs as a comparative group in Negeri Sembilan by simple random sampling method. Personal respirable dust exposure was collected by using air sampling pump. The cement mineral dust were analysed by using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) for Arsenic (As) and Chromium (Cr) while for the Silica (Si) by using X-ray powder Diffraction (XRD) method. IL-8 concentrations were analysed using human ELISA kit while FENO levels and Lung Function test were obtained by using NIOX MINO and Chestgraph H1-105 spirometer. Mean and standard deviation of cement respirable dust was higher in manufacturing workers with 4.94±3.32 mg/m³ and administrative workers with 1.99±2.02 mg/m³ compared with comparative group at 1.18±0.78 mg/m³. Geometric mean (GM) of Si, As and Cr concentrations in manufacturing workers were 5.23 ± 2.29 mg/m³, 0.10 ± 0.02 mg/m³ and 1.51 ± 2.47 mg/m³ respectively. Occurrence of phlegm (χ2=26.868, p= <0.001) and cough (χ2=14.576, p= <0.001) were significantly higher among cement workers compared to the comparative group. Lung function abnormalities of FVC% predicted and FEV₁% predicted showed significantly difference between cement workers and comparative group with (χ2=31.228, p = <0.001) and (χ2=34.855, p = <0.001) respectively. IL-8 and FENO were significantly higher among cement workers with GM, 239.33±1.67 pg/mL and 30.02 ± 26.55 ppb respectively. There was positive correlation between respirable Si and Cr dust with FENO level among administrative workers with (r= 0.646, p=0.004 and r=0.521, p=0.013). There was significant correlation between respirable As dust with IL-8 concentrations among manufacturing workers (r=0.464, p=<0.001). After controlling for confounders, the abnormalities of FVC% predicted and FEV₁% predicted were significantly associated with the respirable Si dust among cement workers (OR=6.913; CI=1.965-24.322 and OR=18.320; CI=3.078-109.027). Production of IL-8 concentrations in manufacturing workers were significantly influenced by the exposure to respirable As dust concentrations and factor of not wearing a mask or respirator (R2=0.402, all p=<0.05). FENO concentrations in administrative workers were significantly influenced by the exposure to respirable Si dust (R2=0.584, p=0.006). The higher concentration of FENO and IL-8 production are the indicator of airways inflammation. Probability of cancer risks for Si, As and Cr VI dust exposure among manufacturing workers were at 4.34 x 10-5, 1.11 x 10-3 and 6.99 x 10-3, respectively after considering the control measures. Exposure to respirable cement dust contributed to a high risk of lung impairment through various respiratory health symptoms, reducing lung function level, increased IL-8 and FENO concentrations. Both manufacturing and administrative workers showed a high prevalence of respiratory disease. Cement workers were at high risk of getting cancerous and non-cancerous diseases while working. It is recommended for the cement industry to improve their control measure on exposure to cement dust and strictly enforce on wearing respirator among workers especially administrative workers.